2013
DOI: 10.1051/ject/201345259
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Approach to Pediatric Modified Ultrafiltration: A Novel Circuit Design

Abstract: A simple intuitive approach to modified ultrafiltration (MUF) may improve the safety of this technique and enhance the adoption rate of MUF in pediatric and adult centers. This simplified technique is more easily implemented than the traditional MUF technique and will allow teams to adopt this technique successfully with ease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The improvements in myocardial and hemodynamic functions after MUF are due to the ability of this procedure to enhance arterial blood pressure, global left ventricular function, cardiac index, systolic arterial pressure, and diastolic and systolic blood pressure [12]. The rationale for using MUF in pediatric patients/neonates is to minimize the risk of CPB-induced pulmonary dysfunction, as indicated by minimized gas exchange, high pulmonary vascular resistance, and compromised pulmonary compliance [13,14]. Several research studies have confirmed the role of MUF in improving static/dynamic lung compliance, minimizing lung injury, and enhancing the overall pulmonary function after cardiac surgery in pediatric patients [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The improvements in myocardial and hemodynamic functions after MUF are due to the ability of this procedure to enhance arterial blood pressure, global left ventricular function, cardiac index, systolic arterial pressure, and diastolic and systolic blood pressure [12]. The rationale for using MUF in pediatric patients/neonates is to minimize the risk of CPB-induced pulmonary dysfunction, as indicated by minimized gas exchange, high pulmonary vascular resistance, and compromised pulmonary compliance [13,14]. Several research studies have confirmed the role of MUF in improving static/dynamic lung compliance, minimizing lung injury, and enhancing the overall pulmonary function after cardiac surgery in pediatric patients [15,16].…”
Section: Introductionmentioning
confidence: 99%